The Effect of Noise in a Performance Measure on Work Motivation - Randolph Sloof; C. Mirjam van Praag (Tinbergen Institute, 2008)
This paper reports the results of an individual real effort laboratory experiment where subjects are paid for measured performance. Measured performance equals actual performance plus noise. We compare a stable environment where the noise is small with a volatile environment where the noise is large. Subjects exert significantly more effort in the volatile environment than in the stable environment. This finding is in line with standard agency theory and contrasts a distinct element of expectancy theory; noisier performance measures do not lower work motivation.
Keywords: C91; J33; M52; 330; Performance measurement; noise; work motivation; experiments; agency theory; expectancy theory; Leistungsmotivation; Performance-Management; Test; Prinzipal-Agent-Theorie; Erwartungstheorie; Theorie